Sayings of Imam Ata explanatory in Surat Al- Imran - Al- Malki, Faisal Bin Salem (Journal of Islamic Sciences, 2019)
This research about the words transferred to us from the follower of Imam Ata ibn Abi Rabah, may God have mercy on him, the main objective of the research: to collect the explanatory sayings of Imam Ata ibn Abi Ribh in Surat Al- Imran from all sources.The problem of research was to extract the quotes that quoted this subordinate, and judge them through the study of attribution.The research revolves around two things:I: About a brief summary of Imam Ata ibn Abi Rabah, and the most prominent elders who took them and his disciples who transferred him.The second: the collection of explanatory sayings of Ata ibn Abi Rabah in Surat Al- Imran books of the adage, highlighting the most important results learned from this research.I have followed the historical inductive analytical approach to reach the research objectives.Has reached the results, the most important: that Imam Ata ibn Abi Rabah, may God have mercy on him has a great virtue and status when the companions honorable, Al- Hasan and the weak ones. I recommend that researchers continue to collect the sayings and narrations of Imam Ata ibn Abi Rabah, may God have mercy on him in all sources and study.
Keywords: Sayings; Ata ibn Abi Rabah; Surat Al- Imran; Judgment on Sindh